Interface Bond Characterization between Fiber and Cementitious Matrix - Won-Chang Choi; Seok-Joon Jang; Hyun-Do Yun (International Journal of Polymer Science)
The use of high performance composite fibers allows for the improvement of the mechanical properties of cement composites. Previous research results indicate that the mechanical properties of such composites are determined predominantly by the interface properties between the fiber and cementitious matrix. Many researchers have conducted single-fiber pull-out tests using cementitious composites to quantify the interfacial properties between the fiber and cement matrix. This paper aims to establish a design methodology that employs coefficients to represent the design parameters for the interfacial properties for three types of fibers: carbon fiber, polypropylene fiber, and twisted wire strand steel cord. The parameters for each type of fiber include the water-to-binder ratio and fiber embedment length. The adopted equation used for the numerical analysis was calibrated using experimental data, and design coefficients are proposed accordingly. The developed models could be validated successfully, and the pull-out characteristics of each fiber type are presented.